1989
DOI: 10.1530/jrf.0.0860001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin- and alloxan-induced diabetes mellitus on mouse follicular and early embryo development

Abstract: Mice were made diabetic by intraperitoneal injection of streptozotocin or alloxan. Germinal vesicle breakdown in the ovarian follicles at 8 h after hCG in control animals (57%) was significantly greater than in streptozotocin-(24%) and alloxan\x=req-\ (42%) diabetic animals (P < 0\m=.\001). This delay in oocyte maturation was reversible by in-vivo insulin administration to diabetic mice. A developmental delay was also found for embryos recovered from diabetic mice. This developmental delay extended into the 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
3
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 29 publications
4
86
3
2
Order By: Relevance
“…Many studies using mouse models of type I diabetes have shown the negative impact of hyperglycemia alone on oocyte maturation. Oocytes from type I diabetic mice exhibit delays in maturation [36][37][38] accompanied by spindle defects and chromosome misalignment during oocyte maturation [37]. Maternal type I diabetes also causes increased granulosa cell apoptosis [37].…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 99%
“…Many studies using mouse models of type I diabetes have shown the negative impact of hyperglycemia alone on oocyte maturation. Oocytes from type I diabetic mice exhibit delays in maturation [36][37][38] accompanied by spindle defects and chromosome misalignment during oocyte maturation [37]. Maternal type I diabetes also causes increased granulosa cell apoptosis [37].…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 99%
“…It is reported that overnight culture of denuded oocytes lead to complete meiosis (98%) at control level, while in COC culture, MII reached oocytes were significantly lowered compared to controls [11]. Powers et al [12], suggest that the decreasing in ovulation rate may be due to impairment of nitric oxide protection, due to a defect in the blood follicle barrier in diabetic ovaries.…”
Section: Discussionmentioning
confidence: 98%
“…Исследования на лабораторных животных показали, что даже кратковременное воздействие гипергликемии у бере-менных самок приводит к задержке развития эмбрионов [36,37]. Эмбрионы, полученные от животных в состоянии острой гипергликемии, вызванной стрептозотоцином или аллоксаном, отличались от эмбрионов здоровых особей сниженной скоро-стью дробления [36].…”
Section: экспериментальные данныеunclassified
“…Эмбрионы, полученные от животных в состоянии острой гипергликемии, вызванной стрептозотоцином или аллоксаном, отличались от эмбрионов здоровых особей сниженной скоро-стью дробления [36]. Было показано, что гипергликемия также оказывает отрицательное влияние на питание и энергетические ресурсы эмбриона в преимплантационный период: у эмбрионов от самок с СД отмечалось снижение утилизации глюкозы, ко-торое было непосредственно связано со снижением транспорта глюкозы как на уровне мРНК, так и на уровне транспортных белков Glut [38].…”
Section: экспериментальные данныеunclassified